2009
DOI: 10.3109/00016340903318014
|View full text |Cite
|
Sign up to set email alerts
|

Facility‐based audit of maternal mortality in Lebanon: A feasibility study

Abstract: A facility-based approach is a potential tool for conducting a national maternal mortality audit in a developing country like Lebanon. Computerized medical records and mandatory participation of hospitals are prerequisites for success. This would require the government to develop a cohesive national policy on reducing maternal mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…There are, however, large variations in MMRs between different EMR countries. Whereas new studies from Lebanon [5], Bahrain [6], and Saudi Arabia [7] have reported lower MMRs than that in the present study (39, 25, and 28 per 100 000 deliveries, respectively), other countries such as Sudan (where sepsis is the leading cause of maternal death) have far higher MMRs (442 per 100 000 live births) [8].…”
contrasting
confidence: 87%
“…There are, however, large variations in MMRs between different EMR countries. Whereas new studies from Lebanon [5], Bahrain [6], and Saudi Arabia [7] have reported lower MMRs than that in the present study (39, 25, and 28 per 100 000 deliveries, respectively), other countries such as Sudan (where sepsis is the leading cause of maternal death) have far higher MMRs (442 per 100 000 live births) [8].…”
contrasting
confidence: 87%
“…Maternal and perinatal death reviews have been conducted in Tanzanian facilities since 2006 and have identified avoidable factors and opportunities for improvement via confidential multidisciplinary team discussions led by healthcare providers and by reviewing patient records [ 28 ]. A Lebanese study mentioned that the FDR approach helped professionals to understand the causes and determinants of maternal mortality [ 29 ]. In Asia, the WHO initiated maternal and perinatal death review at facilities in Bangladesh, Sri Lanka, India, Nepal, Myanmar, Bhutan, the Maldives, Indonesia, Thailand, and Korea [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information might have been missed, particularly if the information of interest was presented as a single word, or only reported once in the entire text [29]. In summary, the information documented within medical charts has been characterized in the literature and through our observations as being poorly maintained and marred with errors, omissions, and idiosyncrasies [26,30,31]. However, the data extractors were still able collect some valuable data and triangulate it with the other information to glean a better picture of what did and did not occur.…”
Section: Discussionmentioning
confidence: 99%